Conservation units as a protection tool for social wasps in Minas Gerais state, Brazil - Oliveira, Glauco Cássio de Sousa; Henriques, Nathália Ribeiro; Clemente, Mateus Aparecido [UNESP]; de Souza, Marcos Magalhães (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2021)
Conservation Units are an important tool for the Brazilian biota protection. However, various taxa, including the social wasps, are undersampled or are unknown in these areas. Therefore, our study aimed to assess the social wasp richness and distribution in the Conservation Units in Minas Gerais state, southeastern Brazil. The social wasps were sampled between 2015 and 2019 in the Ritápolis National Forest (FLONA Ritápolis), in the Alto-Montana Private Natural Heritage Reserve (RPPN Alto-Montana), in the Rio Machado Basin State Environmental Protection Area (APA Rio Machado) and in the Serra de São José Environmental Protection Area (APA Serra de São José), using two different sampling methodologies. Fourteen species were sampled for FLONA Ritápolis, 10 for RPPN Alto-Montana, 35 for APA Rio Machado and 19 for APA Serra de São José. Ninety-six social wasp species of the known richness in Minas Gerais were sampled in 14 Conservation Units, representing 90% of the fauna of the state. Thirty-four species are exclusive to these areas, with emphasis on the Rio Doce State Park, the Serra do Papagaio State Park, the Pandeiros River Wildlife Regufe and the APA Rio Machado. Most of the Conservation Units sampled are in the Atlantic Forest areas, but further efforts are needed in this biome, because of its accelerated destruction. There is still an urgent need for more studies in the Cerrado and Caatinga areas in the state, especially in Conservation Units.
Keywords: Atlantic forest; Caatinga; Cerrado; Insect conservation; Wasp distribution